An examination of education-based dissertation macrostructures. Issue 45 (May 2020) - Anderson, Tim; Alexander, Ian; Saunders, Gillian
Abstract: This article describes a large-scale analysis of dissertation macrostructures in the Faculties of Education at five major Canadian research universities. We draw on van Dijk (1980) and Paltridge (2002) in categorizing the global organizational patterns of 1, 373 PhD dissertations and cross reference these patterns with each study's research perspective. Although prior research has addressed thesis and dissertation writing by drawing on ESP and EAP perspectives, the majority of these studies have focused on individual sections within the larger dissertation text, while little work has considered the macrostructures of these texts, with some notable exceptions (e.g., Paltridge, 2002; Paltridge & Starfield, 2007, 2020; Paltridge, Starfield, Ravelli, & Tuckwell, 2012; Thompson, 1999). No study to date, however, has analyzed the breadth of dissertation macrostructures covered in this project. This research therefore occupies an important space in describing current trends in dissertation writing and research approaches in contemporary educational research from five large English-medium Canadian universities. In so doing, we highlight not only the variety in dissertation writing and doctoral research but, more specifically, the emergence of two new hybrid dissertation macrostructures.